Mechanistic model of combined pressure drop and heat transfer for the entire growth stage of an elongated bubble in a rectangular microchannel. (15th November 2022) - Patra, Chinmaya Kumar; Bhattacharya, Anandaroop; Das, Prasanta Kumar
Highlights: A unified flow boiling model for slug flow regime is developed. The model is based on combined momentum and energy transfer approach. Bubble growth from inception till its departure from microchannel is considered. Thin film evaporation mechanism is considered for modelling the heat transfer. Cyclic passage zones have the most obvious impact on local heat transfer coefficient. Abstract: A one-dimensional flow-boiling model for the slug-flow regime is formulated to describe the pressure drop and heat transfer mechanism in a microchannel of rectangular cross-section. The pressure drop model considers three stages of bubble growth namely: (i) partial confinement, (ii) full confinement and (iii) vapour venting. The heat transfer coefficient at any particular location is obtained by assuming the periodic passage of four zones: (i) liquid slug zone, (ii) elongated bubble zone, (iii) partially dryout zone, and (iv) fully dryout zone. The model is evaluated using constant fluid properties, to study the parametric variation of channel pressure drop and heat transfer coefficient. The effects of variation in channel dimension, flow velocity, heat flux and properties of working fluid on pressure drop and heat transfer coefficient have been studied using the model. The model is capable of simulating all the transport processes for a single bubble from its inception till it leaves the microchannel and thereby it can estimate the pressure drop in the channel along with the heat transfer coefficient i.e. spatially averaged over the channel length and at any location from channel upstream to the downstream end.